Improved ZF-like Intra-Tier Precoder for A VFDM Based Two-Tier System - Yao, Rugui; Jiang, Pengfei; Yao, Lukun; Gao, Yan; Zhang, Yuxin; Zuo, Xiaoya (2018 25th International Conference on Telecommunications (ICT), 2018)
In this paper, we study the design of two improved zero forcing-like (ZF-like) precoders in a two-tier cognitive network, consisting of a macro cell (MC) and multiple small cells (SCs). By exploiting Vandermonde-subspace frequency division multiplexing (VFDM) transmission, the cognitive SCs can coexist with the MC. We first review the cooperative cross-tier precoder (CTP) design to mitigate the interference from the SCs to the MC. The cooperative CTP allows us to use more efficient intra-tier precoder (ITP) in SCs to handle intra-tier interference. Although block-diagonal zero-forcing (BD-ZF) ITP can completely suppress the interference among the SCs, it also causes loss of some transmitted dimensions. Considering this problem, we design the focalized zero-forcing (F-ZF) ITP and regularized zero forcing (R-ZF) ITP precoding schemes. Then, the transmitted dimensions of the three schemes are discussed and compared. Numerical simulation results show that the two improved ZF-like ITPs can significantly improve the capacity of two-tier network.